Are Corporate Carbon Management Practices Reducing Corporate Carbon Emissions?. (28th March 2015) - Doda, Baran; Gennaioli, Caterina; Gouldson, Andy; Grover, David; Sullivan, Rory
ABSTRACT: This paper is the first large scale, quantitative study of the impact of corporate carbon management practices on corporate greenhouse gas (GHG) emissions. Using data for 2009 and 2010 from the Carbon Disclosure Project survey, we find little compelling evidence that commonly adopted management practices are reducing emissions. This finding is unexpected and we propose three possible explanations for it. First, it may be because corporate carbon data and management practice information have not been reported in a standardized way. Second, there may be a delay between the application of corporate carbon management practices and their impact on emissions performance. Third, carbon management practices are not sufficiently impact‐oriented, meaning there is no relationship to observe. Our findings are important for policymakers designing corporate GHG reporting standards, for the multiple stakeholders trying to understand the drivers of corporate carbon performance, and for the corporate managers responsible for measuring, reporting and mitigating emissions. Copyright © 2015 The Authors. Corporate Social Responsibility and Environmental Management published by ERP Environment and John Wiley & Sons Ltd.